Utilizing Authentic Materials to Improve Listening and Speaking Skills: A Narrative Inquiry - Faridah Fauziyah; Sri Sumarni (Indonesian Journal of Foreign Language Studies, 2025)
This study explores the role of authentic materials in enhancing the listening and speaking skills of English learners, focusing on the researcher’s own journey of language improvement. Authentic materials—such as video games, YouTube videos, and movies—offer real-life contextual exposure to language use, which is essential for developing practical communication skills in English. By employing a self-reflection narrative inquiry methodology, this study provides an introspective account of how the researcher engaged in self-directed learning over several years to improve listening and speaking proficiency. The findings of the study indicate that consistent interaction with authentic materials significantly contributed to the enhancement of the researcher’s speaking skills. These materials stimulated more natural language acquisition processes by exposing the learner to genuine conversational scenarios, varied accents, idiomatic expressions, and cultural nuances that are often absent in traditional textbooks. Additionally, regular application and practice of the language skills acquired through these resources reinforced learning and led to measurable progress.Based on these results, the study recommends that English learners and educators integrate diverse authentic materials into language learning curricula and self-study routines to foster more effective listening and speaking abilities. Furthermore, it encourages learners to maintain frequent and purposeful usage of these materials to maximize language retention and fluency. To build on these insights, the study also advocates for further empirical research involving a broader range of authentic material types and different learner populations, which could provide more generalized and comprehensive evidence on the efficacy of authentic resources in language education.